Directions of national development : T. S. Avinashilingam 70th year commemoration volume - Avinashilingam, T. S., 1903-; Rajammal P. Devadas, 1919-; Kuḻantaivēlaṉ, Ka (Sri Ramakrishna Mission Vidyalaya Old Boys Association, 1975)
Festschrift honoring the Indian educationalist, T.S. Avinashilingham, b. 1903.